Design, Planning, Machining, and Manufacturing Using Rapid Prototyping Technologies in Modern Engineering - Md Abdul Basith, Md.Hira Hashimi , (International Journal of Scientific Research and Management (IJSRM), 2017)
The term rapid prototyping (RP) refers to a class of technologies that are used to produce physical objectslayer-by-layer directly from computer aided design (CAD) data. These techniques allow designers toproduce tangible protons of their designs quickly, rather than just two-dimensional pictures. Besidesvisual aids for communicating ideas with co-workers or customers, these prototypes can be used to mostvarious aspects of their design, such as wind tunnel tests and dimensional checks. In addition to theproduction of prototypes, rapid prototyping techniques can also produce molds or mold inserts (rapidtooling) and even fully functional end parts (rapid manufacturing).In rapid prototyping, the term “rapid” is relative; it aims at the automated step from CAD data tomachine, rather than at the speed of the techniques. Depending on the dimensions of the object,production times can be as long as a few days, especially with complex parts or when long cooling timesare required. This may seem slow, but it is still much faster than the time required by traditionalproduction techniques, such as machining. This relatively face production allows analyzing parts in avery early stage of designing, which decreases the resulting design cost. The costs can also be reducedbecause rapid prototyping processes are may automated and therefore, this need the skill of individualcraftsmen for no more than finishing the part.